Susceptibility of anopheles campestris-like and anopheles barbirostris species complexes to Plasmodium falciparum and Plasmodium vivax in Thailand - Thongsahuan S. (2014)
Nine colonies of five sibling species members of Anopheles barbirostris complexes were experimentally infected with Plasmodium falciparum and Plasmodium vivax. They were then dissected eight and 14 days after feeding for oocyst and sporozoite rates, respectively, and compared with Anopheles cracens. The results revealed that Ano-pheles campestris-like Forms E (Chiang Mai) and F (Udon Thani) as well as An. barbirostris species A3 and A4 were non-potential vectors for P. falciparum because 0% oocyst rates were obtained, in comparison to the 86.67-100% oocyst rates recovered from An. cracens. Likewise, An. campestris-like Forms E (Sa Kaeo) and F (Ayuttaya), as well as An. barbirostris species A4, were non-potential vectors for P. vivax because 0% sporozoite rates were obtained, in comparison to the 85.71-92.31% sporozoite rates recovered from An. cracens. An. barbirostris species A1, A2 and A3 were low potential vectors for P. vivax because 9.09%, 6.67% and 11.76% sporozoite rates were obtained, respectively, in comparison to the 85.71-92.31% sporozoite rates recovered from An. cracens. An. campestris-like Forms B and E (Chiang Mai) were high-potential vectors for P. vivax because 66.67% and 64.29% sporozoite rates were obtained, respectively, in comparison to 90% sporozoite rates recovered from An. cracens.